The Influence of Digital Financial Literacy, Social Environment, and Financial Self Efficacy on Online Loans among Generation Z - Nunun, Nunun; Junaidi, Junaidi; Jasman, Jumawan (Jurnal Penelitian Ekonomi dan Bisnis, 2026)
This study aims to describe and analyze the influence of digital financial literacy, social environment, and financial self-efficacy on individuals' decisions to take out online loans. The type of research is quantitative research. The population in this study is Generation Z. The sampling technique used primary data in the form of questionnaires, resulting in 80 respondents. The data collection method used Structural Equation Modeling (SEM) with AMOS 22 and SPSS 22 software. The research results show that: digital financial literacy has a negative and insignificant effect on online loans, the social environment has a positive but insignificant effect on online loans, financial self-efficacy has a positive but insignificant effect on online loans, digital financial literacy has an indirect (full mediation) effect on financial self-efficacy, and the social environment has an indirect (full mediation) effect on financial self-efficacy.